EFESIENSI ANGGARAN OPERASIONAL SEBAGAI ALAT PERENCANAAN PEMASARAN PRODUK PADA CV. AMDK BARIKLANA AL-AMIEN PRENDUAN - Safiuddin, Kamalina Zulfa (Al-Idarah, 2024)
The operational budget is the most important thing in improving a product. The company can get input in improving the operational budget to increase sales at CV. AMDK Barikna Al-Amien Prenduan and loyalty to a product. This research aims to analyze various factors in operational budgeting. This research will analyze operational budget planning factors and the role of operational budgets as a planning tool for bottled drinking water at CV. AMDK Barikna Al-Amien. This type of research is descriptive qualitative research, namely research that aims to understand a phenomenon experienced by research subjects. Data collection methods are interviews, observation and documentation. Interviews were conducted with AMDK Barikna Al-Amien staff. The research results show the factors that influence operational budget planning at CV. BARIKLANA is last year's profit and loss, company policies regarding marketing, service costs and marketing channels, the condition of competitors, the condition of the market environment, the economic condition of the market community. The role of the operational budget is expected to be controlled so that it can increase sales turnover based on planning and regular monitoring in line with the company's activities, where a profit and loss report is made every year and work evaluations are carried out every month.